Automatic Measuring Approach and Device for Mature Rapeseed's Plant Type Parameters. (3rd December 2019) - Xu, Shengyong; Wang, Jinming; Tian, Hao; Wang, Bo
Abstract : The plant type parameters, which can be used to track and study the morphological changes of crop organs, are of great importance for breeders and testers. Based on the structural characteristics of mature rapeseed, an automatic measuring system for rapeseed plant type parameters was studied, through which the parameters of primary branches including their quantity, position, and branching angle and the geometric parameters such as plant height, main stem width, main raceme length, and the first branch height were measured. The system hardware includes a manual cutting-short device, an image acquisition darkroom, and a control circuit, used for capturing videos of a stably rotating rapeseed plant in a darkroom with an adjustable light source. The system software is used to connect and control CCD camera and other hardware and run specific image processing algorithms to process and analyze videos to obtain plant type parameters. The human-machine interface provided by the system can be used to set working parameters and display and process measurement results. To evaluate the accuracy of this prototype, batches of rapeseed plants were tested. The results showed that the mean absolute percentage error (MAPE) for the system was about 2.74%, and the automatic measurements had a good agreement with manual measurements. The measuring efficiency was approximately 2.1 times over manual method. In conclusion, the system, which automatically extracts plant type parameters with high throughput and high precision, is of practical value as it can effectively reduce the labor intensity of researchers and provide important basic data for the research of rapeseed breeding and agricultural machinery design.